Pengaruh Kualitas Layanan, Harga Dirasakan Dan Keadilan, Dan Kenyamanan Layanan Terhadap Loyalitas Konsumen Dan Kepuasan Pelanggan Sebagai Mediasi (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Surakarta) - Widihastuti, Linda, Soepatini, SE., M.Si., Ph.D (2017)
The college is an institution that has a role and strategic position in the macro education goals that need to make improvements continuously to realize the quality of human resources. For it is in dire need of human resource management quality. The level of student satisfaction towards a service will give a reflection of the success in the college in providing these services. Complaints student at Muhammadiyah University of Surakarta had a lot of variety. This study aims to determine whether the customer loyalty is influenced by the quality of service, price and perceived fairness, convenience mediated services and customer satisfaction. The population in this study were students of the Faculty of Economics and Business at the University of Muhammadiyah Surakarta. Samples taken as many as 125 respondents using quota sampling technique. Data was collected using a survey method through questionnaires filled out by respondents. Then the data were analyzed using path analysis (path analysis) with the help of multiple linear regression and Sobel test. This analysis includes the Test Validity, reliability testing, Classical Assumption Test and Path Analysis. Test the hypothesis by t test and F test, as well as the coefficient of determination (R2). The analysis showed that: (1) the quality of services and significant positive effect on customer loyalty proved of value for t> t table (2.220>1.984) with significant value 0.028<(0.05), (2) the price and the perceived fairness significant effect customer loyalty proved of value for t> t table (-2.252>1.984) with significant value 0.026<(0.05), (3) the comfort of the service significant positive effect on customer loyalty proved of value for t> t table (2.712>1.984) with a significance value of 0.008<(0.05), (4) customer satisfaction and significant positive effect on customer loyalty proved of value for t> t table (3,092>1,984) with a significance value of 0.002<(0,05), (5) the service quality affects customer loyalty through customer satisfaction is evidenced from t value 7.676>1.984 with a significance level of 0.05, (6) the price and the perceived fairness effect on consumer loyalty through customer satisfaction is evidenced from the t value - 15.849>1.984 with a significance level of 0.05, (7) the convenience of service affects customer loyalty through customer satisfaction is evidenced from t value 2.715>1.984 with a significance level of 0.05